(13x-25)=(9x-1)

Simple and best practice solution for (13x-25)=(9x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (13x-25)=(9x-1) equation:



(13x-25)=(9x-1)
We move all terms to the left:
(13x-25)-((9x-1))=0
We get rid of parentheses
13x-((9x-1))-25=0
We calculate terms in parentheses: -((9x-1)), so:
(9x-1)
We get rid of parentheses
9x-1
Back to the equation:
-(9x-1)
We get rid of parentheses
13x-9x+1-25=0
We add all the numbers together, and all the variables
4x-24=0
We move all terms containing x to the left, all other terms to the right
4x=24
x=24/4
x=6

See similar equations:

| -8-3n=4 | | 13x-25)=(9x-1) | | 30=450+150m | | -3(x+2=-12 | | x+x-10+.90=180 | | 2/5x+38=-12 | | 5z2+33z+18=0 | | 30=450m+150 | | -14p+12=-20+18p | | 30=450m+250 | | 4n+4=53-3n | | 5b+b+4b=40 | | 150=450m+30 | | g/4-45=40 | | x+13=169 | | 2x-3+x+7=180 | | 7u=9u+8 | | 450=150m+30 | | 5.7t-18.8=15.1t | | q/9+70=65 | | -8=-2m-9 | | q=14+3q | | 20+13q=-16+15q | | 250=45p+5 | | 40x=100+15x* | | 32+m=307 | | 10x/4+2X/8-16=3x/2+40 | | 96=1/3×6^2h | | 3(u-4)-3=-5(-2u+6)-u | | s/4+5=2 | | 5p-5=6-4p | | -3u+2/3=-4/3u-7/5 |

Equations solver categories